Supporting and Inhibiting Factors of Outdoor STEAM Learning in Early Childhood Education - Munawar, Muniroh; Setyoadi, Yuris; Afif Luthfy, Perdana; Prasetyawati, Dwi (KnE Social Sciences, 2024)
Research shows that it’s important for kids to get out and play. By combining outdoor learning and STEAM, it will provide a new perspective on the lesson theme and can connect school content with the real-world problems. However, some things support and hinder outdoor STEAM learning in early childhood education. This study aims to determine the supporting and inhibiting factors of STEAM outdoor learning in early childhood education. The subjects of this research were 34 early childhood education schools in Central Java. This research data is qualitative, collected through observation, documentation, and interviews techniques. The observation technique was used to make direct observations in the field and documented them in the form of videos and photos. Research data management was carried out using the QSR NVivo software. The data analysis technique used was the qualitative data analysis technique from Miles and Huberman which includes data reduction, data presentation, and drawing conclusions. Testing the validity of the data in this research used source triangulation techniques through the cluster analysis and comparison diagram features in the QSR NVivo software. Based on the coding result of the research data using the help of NVivo QSR software, it is known that the biggest supporting factors of outdoor STEAM learning in early childhood education are environment, media, teachers, and infrastructure, while other supporting factors are area, cost, weather, new ideas, new experiences, and situations. The biggest inhibiting factors of outdoor STEAM learning in early childhood education are adaptability, security, and infrastructure, while other inhibiting factors areweather, support; environment, pollution, and situation. The results of this study can be used as a guideline for outdoor STEAM learning in early childhood education and make the inhibiting factors a challenge for teachers to facilitate outdoor learning as a form of maximizing the use of the environment as a learning resource in early childhood education. Keywords: STEAM, outdoor learning, early childhood education